An Optimal Precursor of Northeast Pacific Marine Heatwaves and Central Pacific El Niño Events. Issue 5 (10th March 2022) - Capotondi, A.; Newman, M.; Xu, T.; Di Lorenzo, E.
Abstract: The intensity of Northeast Pacific marine heatwaves (MHWs) has been related to local stochastic atmospheric forcing with limited predictability, but their evolution and persistence may be controlled by large‐scale climate influences. A Linear Inverse Model containing both sea surface temperature and sea surface height (SSH) anomalies is used to identify the "optimal" conditions for observed Northeast Pacific MHW events that developed two‐to‐four seasons later. These optimal initial conditions include SSH anomalies that are responsible for most of the MHW growth, suggesting the relevance of subsurface ocean dynamics. Moreover, Northeast Pacific MHW growth occurs as part of a basin‐scale dynamical mode that links the North Pacific to central equatorial Pacific El Niño events, whose subsequent development may lengthen MHW duration. Plain Language Summary: The Northeast Pacific Ocean has experienced episodes of intense and persistent abnormally warm conditions, also known as marine heatwaves (MHWs), with devastating ecological impacts. Being able to predict these extreme events a few seasons in advance is therefore very important, but has proven elusive. Understanding why marine heatwaves differ from one event to the next, especially in terms of their strength and how long they last, is limited due to our inability to predict aspects of daily weather that help drive these events. However, whether a new marine heatwave might occur, and if so how it might then evolve, may be partly understood by relating it to climate conditions extending throughout the Pacific. In this study, we use an empirical method to construct a model capturing how such climate conditions may change over time, and therefore whether a marine heatwave could be anticipated. Our model finds specific ocean surface conditions appearing to lead to the development of the Northeast Pacific marine heatwaves 6–12 months later. These conditions are related to a unique pattern of sea surface anomalies spanning the North Pacific and the central tropical Pacific, which also links extra‐tropical marine heatwaves with subsequent tropical central Pacific warming. Key Points: A large‐scale precursor to Northeast Pacific marine heatwaves (MHWs) with anomalies in both the North and Tropical Pacific is identified This optimal precursor includes initial sea surface height anomalies that are key to MHW growth The initial condition leading to optimal development of Northeast Pacific MHWs can also lead to subsequent Central Pacific El Niño events